Efficacy and Safety of Fluocinolone Acetonide Implant in Diabetic Macular Edema: Practical Guidelines from Reference Center - Lucas Sejournet; Thibaud Mathis; Victor Vermot-Desroches; Rita Serra; Ines Fenniri; Philippe Denis; Laurent Kodjikian (MDPI AG, 2024)
Diabetic macular edema (DME) is a common complication of diabetic retinopathy. Treatment with intravitreal injections is effective in most cases but is associated with a high therapeutic burden for patients. This implies the need for long-term treatments, such as the fluocinolone acetonide (FAc) implant. A review of basic science, pharmacology, and clinical data was conducted to provide a state-of-the-art view of the FAc implant in 2024. Although generally well tolerated, the FAc implant has been associated with ocular hypertension and cataract, and caution should be advised to the patients in this regard. By synthesizing information across these domains, a comprehensive evaluation can be attained, facilitating informed decision-making regarding the use of the FAc implant in the management of DME. The main objective of this review is to provide clinicians with guidelines on how to introduce and use the FAc implant in a patient with DME.